2D Palladium Diselenide: Giant Thickness‐Tunable Bandgap and Robust Air Stability of 2D Palladium Diselenide (Small 19/2020). Issue 19 (14th May 2020) - Xie, Chunyu; Jiang, Shaolong; Gao, Yinlu; Hong, Min; Pan, Shuangyuan; Zhao, Jijun; Zhang, Yanfeng
Abstract : In article number 2000754, Jijun Zhao, Yanfeng Zhang, and co‐workers achieve onsite characterizations of the atomic‐scale structure of few‐layer PdSe2 synthesized on Au foils, and establish a one‐to‐one correspondence between the electronic bandgap and thickness from bilayer to bulk by using scanning tunneling microscopy/spectroscopy. The robust air stability of PdSe2 is also demonstrated by the atom‐scale images in long‐time air‐exposed samples.